2018
DOI: 10.1128/aac.00097-18
|View full text |Cite
|
Sign up to set email alerts
|

TonB-Dependent Receptor Repertoire of Pseudomonas aeruginosa for Uptake of Siderophore-Drug Conjugates

Abstract: The conjugation of siderophores to antimicrobial molecules is an attractive strategy to overcome the low outer membrane permeability of Gram-negative bacteria. In this Trojan horse approach, the transport of drug conjugates is redirected via TonB-dependent receptors (TBDR), which are involved in the uptake of essential nutrients, including iron. Previous reports have demonstrated the involvement of the TBDRs PiuA and PirA from Pseudomonas aeruginosa and their orthologues in Acinetobacter baumannii in the uptak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(114 citation statements)
references
References 49 publications
4
104
1
3
Order By: Relevance
“…Because the Ton system can uptake other metabolites (e.g., vitamin B12), the identification of this transport pathway suggests only the potential for the transport of siderophores, hemes, and iron from transferrin/lactoferrin; it is the sole system known to transport these iron-bearing molecules, thus far, in Gram-negative bacteria (Faraldo-Gómez and Sansom, 2003;Caza and Kronstad, 2013). For example, Pseudomonas aeruginosa PAO1 encodes 34 different TonB-dependent receptors, including PiuA and PirA (Luscher et al, 2018). While this diversity of TonB-dependent receptors reflects, in part, an ability to uptake multiple types of siderophores, it also indicates that these receptors are also likely utilized for purposes outside of iron metabolism.…”
Section: Hmm Development: Siderophore and Heme Transportmentioning
confidence: 99%
“…Because the Ton system can uptake other metabolites (e.g., vitamin B12), the identification of this transport pathway suggests only the potential for the transport of siderophores, hemes, and iron from transferrin/lactoferrin; it is the sole system known to transport these iron-bearing molecules, thus far, in Gram-negative bacteria (Faraldo-Gómez and Sansom, 2003;Caza and Kronstad, 2013). For example, Pseudomonas aeruginosa PAO1 encodes 34 different TonB-dependent receptors, including PiuA and PirA (Luscher et al, 2018). While this diversity of TonB-dependent receptors reflects, in part, an ability to uptake multiple types of siderophores, it also indicates that these receptors are also likely utilized for purposes outside of iron metabolism.…”
Section: Hmm Development: Siderophore and Heme Transportmentioning
confidence: 99%
“…To resolve this question, we performed phylogenetic analysis on these transporters in the context of a panel of diverse TBDTs of known structure and/or function. This analysis revealed that while Cir and FepA belong to the same clade of our TBDT phylogram, Fiu belongs to a distal clade with the TBDTs PiuA and PiuD that also mediate catecholate transport [30,33] ( Figure 1A). Wider analysis of this Fiu/Piu clade, identified by HMMER search reveals that related sequences are widespread in proteobacteria ( Figure S1, Table S1, Table S2).…”
Section: Fiu Is a Member Of A Distinct Clade Of Iron-catecholate Tranmentioning
confidence: 84%
“…The disorder of the plug domain loop in crystal state 1, opens a large cavity in the interior of Fiu to the external environment, while in crystal state two this cavity is present, but occluded in the lumen of the Fiu barrel ( Figure 2B). Interestingly, analysis of the structures of PiuA from Acinetobacter baumannii and, PiuA and PiuD from P. aeruginosa revealed analogous crystal states to Fiu ( Figure S3A) [30,33]. In PiuA from A. baumannii all extracellular loops are ordered with the plug loop occluding the entrance to an internal cavity ( Figure S3).…”
Section: Crystal Structures Of Fiu Reveals a Large Gated Internal Chmentioning
confidence: 96%
See 1 more Smart Citation
“…Their orthologues in P. aeruginosa (PiuA and PirA) were proven to be not essential for cell viability because a piuA-pirA double mutant was already obtained (57). In addition, two other genes, ZMO0188 and ZMO1631, in the Z. mobilis ZM4 genome also encode orthologues of TonB-dependent siderophore receptor (26) that might play the similar role as ZMO1815 and ZMO1822 do.…”
Section: Deletion Of Large Genomic Fragment By Repurposing the Endogementioning
confidence: 99%